The effect of rebranding on brand equity and consumer preferences at ACE Hardware Indonesia - Sheril Haeril; Mohamad Sajili (Pusat P2M Politeknik Negeri Batam, 2026)
Brand identity transition is a crucial strategy for companies to maintain market relevance, but studies on its impact on consumer preferences as direct outputs are limited. This study aims to analyze the effect of PT Aspirasi Hidup Indonesia Tbk's rebranding from ACE Hardware to AZKO on brand equity and consumer preferences, to address the research gap regarding consumer behavior following the brand transition. Using a quantitative approach, data were collected from 151 respondents in the Greater Jakarta area via purposive sampling. Data analysis was carried out using the Structural Equation Modeling (SEM) method based on SmartPLS 4.1.1.6. The results show that rebranding has a positive and significant effect on brand equity and consumer preferences. The key findings of this study reveal that rebranding has a stronger influence on consumer preferences (β=0.673) than on brand equity (β=0.618). The novelty of this research lies in proving that the new philosophy of